Application of Maggot Used Organic Fertilizer (Kasgot) in Food Crops and Horticulture Cultivation - Purwanto; Nurchasanah, Siti; Naila Khusna Syarifah, Risqa; Na'imatul Bayyinah, Lafi; Hanifa, Hana; Rahayuaningsih Ratnaningsih, Hanim (Prospect: Jurnal Pemberdayaan Masyarakat, 2024)
This community service was aimed to socialize and apply maggot frass as organic fertilizer in the cultivation of food crops and horticulture in the "Tani Sejahtera" Farmer Group, Tambaksari Kidul Village, Kembaran District, Banyumas Regency. This community service activity was carried out at the 'Tani Sejahtera' Farmer Group, Tambaksari Kidul Village, Kembaran District, Banyumas Regency from June to August 2024. Lecture and discussion methods were used as interactive and two-way information transfer media, then self-help demonstration plots were carried out. The results of the activity showed that farmers were able to absorb material about the potential of maggot frass as a source of organik fertilizer. Farmers voluntarily carried out self-help demonstration plots with commodities developed including corn, cucumber, basil and rice. The maggot frass used has met the technical standards as organik fertilizer according to the Decree of the Minister of Agriculture No. 261 / KPTS / SR.310 / M / 4/2019.